New contributions to the understanding of kiruna-type iron oxide-apatite deposits revealed by magnetite ore and gangue mineral geochemistry at the el romeral deposit, chile - Rojas, Paula A; Barra-Pantoja, Luis Fernando; Deditius, Artur; Reich, Martín; Simon, Adam; Roberts, Malcolm; Rojo, Mario; Arce, M (2014)
Iron oxide-apatite (IOA) or Kiruna-type deposits are an important source of iron and other elements including REE, U, Ag, and Co. The genesis of these deposits remains controversial, with models that range from a purely magmatic origin to others that inv Regular FONDECYT FONDECYT